The Influence of Job Satisfaction and Competence on Auditor Performance - Irtanti, Sri; Khaerudin, Khaerudin (Dinasti Publisher, 2025)
This study aims to examine the influence of job satisfaction and competence on the performance of auditors. Auditor performance is a critical factor in maintaining the quality and reliability of financial reports and ensuring compliance with applicable auditing standards. Auditors often face significant work pressures, such as tight deadlines, complex regulations, and demands for transparency, which can negatively impact their performance if not properly managed. This study employs a bibliometric method using the VOSviewer software to analyze academic journal articles published between 2020 and 2024. Data were collected from Google Scholar, and 22 relevant articles were selected for detailed review. The findings indicate that both job satisfaction and competence have a significant and positive impact on auditor performance. Visualizations generated by VOSviewer software illustrate the interconnectedness of job satisfaction, competence, and other factors influencing auditor performance. High levels of job satisfaction are associated with increased organizational commitment, enhanced motivation, and lower turnover intentions, contributing to better overall performance. Meanwhile, competence improves work efficiency, decision-making quality, and fosters a collaborative and supportive work environment. The study emphasizes the importance of addressing both job satisfaction and competence as key strategies to enhance auditor performance, which in turn strengthens the effectiveness of auditing processes and contributes to improved organizational outcomes.